2020
DOI: 10.26434/chemrxiv.13174601.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong Electronic Coupling of Graphene Nanoribbons onto Basal Plane of Glassy Carbon Electrode

Abstract: The electrochemical behavior of graphene nanoribbons deposited onto glassy carbon electrode using pi-stacking interactions was investigated. We illustrate here that strong electronic communication could be achieved with basal plane of glassy carbon using simple electrochemical treatment.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
2
2
0
Order By: Relevance
“…Our assignment for bpm electrochemistry was thus slightly modified from our original work, where only two distinct pH regions were identified. 57 The updated model presented here is more consistent with additional theoretical modeling and SEC results.…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our assignment for bpm electrochemistry was thus slightly modified from our original work, where only two distinct pH regions were identified. 57 The updated model presented here is more consistent with additional theoretical modeling and SEC results.…”
Section: Introductionsupporting
confidence: 78%
“…The cathodic-to-anodic peak-to-peak separation observed in GNR-2DNS varied between 30-50 mV, indicating a small kinetic barrier associated with the observed charge transfer process and strong electronic coupling of GNR-2DNS with the glassy carbon electrode. In our previous study, 57 we observed similar "strongly coupled" responses for GNR samples drop-casted onto the electrode surface. However, in the previous study, electrochemical pre-treatment was required to disperse the "weakly-coupled" GNR aggregates and form GNR monolayers in strong electronic communication with the electrode.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations